2003
DOI: 10.1001/archinte.163.17.2006
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Aspirin in the Primary Prevention of Cardiovascular Disease

Abstract: The current totality of evidence provides strong support for the initial finding from the Physicians' Health Study that aspirin reduces the risk of a first MI. For apparently healthy individuals whose 10-year risk of a first coronary event is 10% or greater, according to the US Preventive Services Task Force and the American Heart Association, the benefits of long-term aspirin therapy are likely to outweigh any risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
9

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(133 citation statements)
references
References 14 publications
1
123
0
9
Order By: Relevance
“…A meta-analysis of primary cardiovascular event prevention trials in the general population (of whom 80% were men) demonstrated that low-dose aspirin decreases the first MI rate by 32% (relative risk [RR] 0.68, 95% CI 0.59-0.79) but has no effect on the risk of first stroke or cardiovascular death prevention (31). However, the recent Womens' Health Study (WHS) demonstrated that low-dose aspirin reduces the risk of first stroke by 17% (RR 0.83, 95% CI 0.69-0.99) (P ϭ 0.04) but has no effect on the risk of first MI (in individuals Ͻ65 years) or cardiovascular death prevention (32).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of primary cardiovascular event prevention trials in the general population (of whom 80% were men) demonstrated that low-dose aspirin decreases the first MI rate by 32% (relative risk [RR] 0.68, 95% CI 0.59-0.79) but has no effect on the risk of first stroke or cardiovascular death prevention (31). However, the recent Womens' Health Study (WHS) demonstrated that low-dose aspirin reduces the risk of first stroke by 17% (RR 0.83, 95% CI 0.69-0.99) (P ϭ 0.04) but has no effect on the risk of first MI (in individuals Ͻ65 years) or cardiovascular death prevention (32).…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of cardiovascular events through aspirin use is well studied in the general population. In a meta-analysis of 55,580 randomised participants (11,466 women), aspirin treatment was associated with a statistically significant 32% reduction in the risk of a first myocardial infarction and a 15% reduction in all important vascular events, but did not have any significant effects on non-fatal stroke or vascular death [80]. A position statement by the ADA recommended aspirin therapy for primary prevention in diabetic individuals with the following risk factors: a family history of CHD, smoking, hypertension, obesity, microalbuminuria and dyslipidaemia [81].…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%
“…11 More recent analysis of the published literature suggested that the indications for aspirin use should be expanded to primary prevention in populations at high risk, such as those with diabetes, peripheral vascular disease, carotid stenosis, endstage renal disease, 12,13 or polycytemia vera. 14 Of paramount importance are the results of the ISIS-2 trial, which showed that aspirin reduces the mortality from acute MI to an extent that is similar to that of the thrombolytic agent streptokinase.…”
Section: Aspirinmentioning
confidence: 99%